Hedging, ambiguity, and the reversal of order axiom - Oechssler, Joerg; Rau, Hannes; Roomets, Alex (Games and economic behavior, 2019)
We ran experiments that gave subjects a straight-forward and simple opportunity to hedge away ambiguity in an Ellsberg-style experiment. Subjects had to make bets on the combined outcomes of a fair coin and a draw from an ambiguous urn. By modifying the timing of the draw, coin flip, and decision, we are able to test the reversal-of-order axiom. Our main result is that the reversal-of-order axiom seems to hold. We also confirm low levels of ambiguity hedging despite the relative obviousness of the opportunity.
Gesehen am 02.09.2019